Answer:
-9, 3 and 6
Explanation:
Given cubic polynomial equation:
![x^3-63x+162=0](https://img.qammunity.org/2023/formulas/mathematics/college/ut697b2nztkyunmkm10aulhrvni6682jjk.png)
- Let α = first zero
- Let β = second zero
- Let 2β = third zero (since one zero is double another zero).
![\textsf{The sum of the zeros of a cubic polynomial }ax^3+bx^2+cx+d \textsf{ is }-(b)/(a).](https://img.qammunity.org/2023/formulas/mathematics/college/nlabmkr5u0kcvso5fruhv4gvbiei50p868.png)
![\implies \alpha + \beta + 2 \beta = -(0)/(1)](https://img.qammunity.org/2023/formulas/mathematics/college/85au7p8knuu0mr978jhq0ztatfdiag1pcs.png)
![\implies \alpha + 3 \beta = 0](https://img.qammunity.org/2023/formulas/mathematics/college/22u5ctfyh508zil8lckwcdszpdfnxu3qxg.png)
![\implies \beta=- (\alpha)/(3)](https://img.qammunity.org/2023/formulas/mathematics/college/83odpe0upf8oneedjnw771i6ottcurv7of.png)
![\textsf{The product of the zeros of a cubic polynomial }ax^3+bx^2+cx+d \textsf{ is }-(d)/(a).](https://img.qammunity.org/2023/formulas/mathematics/college/b6zs15dzmo8c325d8lgdogwkow03q4962l.png)
![\implies \alpha \cdot \beta \cdot 2\beta=-(162)/(1)](https://img.qammunity.org/2023/formulas/mathematics/college/8l2x337i3pqc3en4qqg609uay0drwddn37.png)
![\implies 2\alpha\beta^2=-162](https://img.qammunity.org/2023/formulas/mathematics/college/5jvjz88ih127clmolb0orbnbmlgckspukf.png)
Substitute the found expression for β into the product equation:
![\implies 2\alpha\beta^2=-162](https://img.qammunity.org/2023/formulas/mathematics/college/5jvjz88ih127clmolb0orbnbmlgckspukf.png)
![\implies 2\alpha\left(- (\alpha)/(3)\right)^2=-162](https://img.qammunity.org/2023/formulas/mathematics/college/t9cl9bmfj4ozb3wutbdyu4fftnwwghrd7o.png)
![\implies 2\alpha\left((\alpha^2)/(9)\right)=-162](https://img.qammunity.org/2023/formulas/mathematics/college/lx79kjrj1zn87mxw8g8cjruwpan1ipa7nr.png)
![\implies (\alpha^3)/(9)\right)=-81](https://img.qammunity.org/2023/formulas/mathematics/college/z8akqzbrvzfarcpnvxycl8rqkhq0ctt4kr.png)
![\implies \alpha^3=-729](https://img.qammunity.org/2023/formulas/mathematics/college/ip5y4c2xtzshzif3j6tm8yqtjsoogcn0t9.png)
![\implies \alpha=\sqrt[3]{-729}](https://img.qammunity.org/2023/formulas/mathematics/college/7ihnkpsfp60dep2ayplk33akux302sll37.png)
![\implies \alpha=-9](https://img.qammunity.org/2023/formulas/mathematics/college/5hgb64garx0n415i93zmpmko8zd95bf2cj.png)
Substitute the found value of α into the expression for β :
![\implies \beta=- (-9)/(3)=3](https://img.qammunity.org/2023/formulas/mathematics/college/z13y4pvafb2p7nvva5viu3j5d0h6qqxf4a.png)
Therefore, the zeros are:
![\implies \alpha=-9](https://img.qammunity.org/2023/formulas/mathematics/college/5hgb64garx0n415i93zmpmko8zd95bf2cj.png)
![\implies \beta=3](https://img.qammunity.org/2023/formulas/mathematics/college/i9nu6ugcurcewr8mtimqlczqggjie402i6.png)
![\implies 2\beta=6](https://img.qammunity.org/2023/formulas/mathematics/college/e8cjvrnind6j49gx3axjeka06bjy94v6wq.png)